Determination of serum cholestane-3β, 5α, 6β-triol by gas chromatography–mass spectrometry for identification of Niemann-Pick type C (NPC) disease. Issue 169 (May 2017) - Kannenberg, Frank; Nofer, Jerzy-Roch; Schulte, Erhard; Reunert, Janine; Marquardt, Thorsten; Fobker, Manfred
Highlights: Simple and inexpensive diagnostic tool for routine hospital laboratory. Serum cholestane-3β, 5α, 6β-triol as an biomarker for NPC diagnosis. Abstract: Niemann-Pick type C (NPC) is a neurological disease caused by an intracellular cholesterol accumulation. Cholesterol oxidation product cholestane-3β, 5α, 6β-triol (C-triol) serves as diagnostic biomarker for NPC, but its measurement in the routine laboratory remains difficult. We developed an isotope dilution gas chromatography–mass spectrometry (GC–MS) method permitting screening for NPC in plasma. 1440 plasma samples obtained from clinically suspicious patients were subjected to alkaline saponification. C-triol was extracted with carbon tetrachloride, transformed into the trimethylsilylethers, separated on a fused silica capillary column with a nonpolar silicone stationary phase, and analyzed by GC–MS. NPC diagnosis was confirmed by DNA sequencing. The method was linear over a concentration range of 0.03–200 ng/mL with a mean recovery rate of 98.6%. The intra- and inter-day variation coefficients assessed at two concentrations were below 15%. Limits of quantification (LOQ) and detection (LOD) were 0.03 ng/mL and 0.01 ng/mL, respectively. Receiver operating characteristic (ROC) analysis estimated that the area under curve was 0.997 implying a significant discriminatory power to identify subjects with NPC. Nevertheless, 13 NPC patients and 29 control subjects confirmed by sequencing showed false negative or positive results, respectively. Two patients with cerebrotendinous xanthomatosis showed a 5–10-fold increase in C-triol levels. We developed a quick and sensitive GC–MS method for determination of C-triol, which may serve as a simple and inexpensive diagnostic tool aiding NPC diagnosis in a routine hospital laboratory. As C-triol elevation is not limited to NPC, the NPC diagnosis has to be confirmed by DNA sequencing.